Gabon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
Efficiency and equity reasons suggest placing a high priority on ensuring that fiscal policy is on a sustainable path. This chapter has sought to estimate the sustainable long-term non-oil primary deficit and the optimal adjustment path toward that level. The banks' inability to monitor effectively the quality of their loan portfolios, paired with the high interest-rate floor on deposits, are key factors behind the very low degree of financial intermediation. The reform of fuel price subsidies in Gabon is necessary to facilitate pro-poor economic growth.